Effect of stretching, strengthening exercises and walking on the management of restless legs syndrome: A cross sectional study - El-Gendy , Salwa R.; Alkhateeb, Afnan M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Background: Restless Leg Syndrome (RLS) is one of the most common causes of sleep disorders that cause functional disability in the lower limb. Due to it is self-limiting, it forces the person to seek treatment. Unfortunately, most of the times, it is misdiagnosed by the doctors and even if it is diagnosed, till date there is no guide program or treatment in the physical therapy. There is huge dearth of knowledge regarding benefits of physical therapy in RLS. Objective: The aim of the present study was to investigate the effect of stretching, strengthening exercises as well as walking on RLS symptoms. Also, to find out the impact of muscle strength and flexibility in relation to the severity of RLS symptoms. Methods: An inquiry of 418 questionnaires randomly distributed was done. A total of 20 participants diagnosed with Restless Leg Syndrome were included in the current study. Pre-post assessment was done for range of motion (by goniometer), functional testing of the foot and ankle, RLS rating scale and RLS ordinal scale. Six participants received physical therapy program for a total of 4 weeks. Twenty patients who had one visit to have the measurement were studied for the correlation study. Results: There was a significant correlation between leg muscles flexibility, strength and the severity of the symptoms. Also, there was a highly significant alleviation of symptoms in the other 6 patients. Conclusion: It can be concluded that physical therapy is effective in relieving symptoms of RLS.